1969
DOI: 10.1111/j.1748-1716.1969.tb04412.x
|View full text |Cite
|
Sign up to set email alerts
|

Intercostal‐to‐Phrenic Reflexes in the Spinal Cat

Abstract: The diaphragm, which previously has been shown to contain relatively few proprioceptors and to lack autogenetic facilitation, was found to be under reflex control from intercostal afferents. Electrical stimulation of the intercostal nerves of the lowest thoracic segments elicited a polysynaptic reflex excitation of phrenic motoneurones followed by a depression of ‘spontaneous’ phrenic motor activity. No phrenic responses were elicited from the upper thoracic segments. Increased phrenic activity was also elicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(43 citation statements)
references
References 19 publications
1
42
0
Order By: Relevance
“…In additional experiments, REMMERS [8] and DECIMA et al [21] have reported a similar inhibition of the diaphragm during electrical stimulation of group I and II afferent fibres in external intercostal nerves. Since this inhibitory response was also observed during high-frequency mechanical vibration of the ribs and was accentuated by the administration of succinylcholine, it was attributed to the stimulation of intercostal muscle spindles [7].…”
Section: Discussionmentioning
confidence: 77%
“…In additional experiments, REMMERS [8] and DECIMA et al [21] have reported a similar inhibition of the diaphragm during electrical stimulation of group I and II afferent fibres in external intercostal nerves. Since this inhibitory response was also observed during high-frequency mechanical vibration of the ribs and was accentuated by the administration of succinylcholine, it was attributed to the stimulation of intercostal muscle spindles [7].…”
Section: Discussionmentioning
confidence: 77%
“…In order to test the effect of muscle stimulation, it was therefore necessary to induce prior activation of phrenic discharge by means of the intercostal-to-phrenic reflex, which was stimulated in three ways. Two were mechanical, involving regular and rhythmic manual compression of the lower thorax posteriorly or rhythmic tapping by means of a metal bar of the lower thorax anteriorly (Decima et al 1969). For the third, one or more intercostal nerves (T9-T10) were exposed, cut distally and the central ends placed on stimulating electrodes.…”
Section: Methodsmentioning
confidence: 99%
“…Such a conclusion does not rule out the possibility, however, that there is a direct spinal reflex component of the respiratory response to stimulation of leg muscle afferents. There are precedents for this hypothesis in that stimulation of receptors in the intercostal muscles or their afferents do have a spinally mediated facilitatory effect on phrenic motoneurones in spinal cats (Downman, 1955;Decima, von Euler & Thoden, 1969;Remmers, 1973), although in animals with intact ponto-medullary control centers the net effect is inhibitory.…”
Section: Introductionmentioning
confidence: 99%
“…The excitatory response of diaphragmatic EMG to chest compression may correspond to the spinal intercostal-to-phrenic reflex arising from caudal intercostal afferents (Decima, Euler & Thoden, 1969 Decerebrate preparations (protocols 2 and 3). The respiratory pattern was unequivocally altered in fourteen of fifteen animals subjected to combined lateral cervical cord lesion and decerebration.…”
Section: Resultsmentioning
confidence: 99%